2014
DOI: 10.1093/chromsci/bmu002
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Method for the Simultaneous Analysis of Fluoroquinolones and Oxazolidinones in Plasma

Abstract: A chromatographic method was implemented and validated for the simultaneous determination of antimicrobials proposed for the treatment of mycetoma: three fluoroquinolones: ciprofloxacin, moxifloxacin and sparfloxacin; two oxazolidinones: DA-7157 (DA2; torezolid) and its prodrug DA-7218 (DA1). Separation of analytes was achieved on an Atlantis dC18 column (150 × 4.6 mm i.d., 5 µm particle size) with a mobile phase composed of acetonitrile and trifluoroacetic acid 0.1% (v/v) using a gradient program. Total runni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Moxifloxacin is chemically known as [1-Cyclopropyl-b-fluoro-1, 4-dihydro-8-methoxy-7-[(4aS, 7aS)-octahydro-6H-pyrrolo [3,[4][5][6] pyridine-6-yl]-4-oxo-3-quinoline carboxylic acid, is a fluoroquinolone broad-spectrum antibiotic agent and used in conjunctivitis. A few analytical techniques have been constructed for quantification of several drugs based on literature survey such as UV Spectrophotometry [33][34][35][36] RP-HPLC [37][38][39][40] , HPLC [41][42] , HPLC-MS [43][44] , LC-MS 45 , LC 46 , chemiluminescence 47 , Tanden mass spectrometry 48 methods for determination of Moxifloxacin have been reported.…”
Section: Gemifloxacin Chemically Is [{Rs}7-[{4z}-3-{aminomethyl}-mentioning
confidence: 99%
“…Moxifloxacin is chemically known as [1-Cyclopropyl-b-fluoro-1, 4-dihydro-8-methoxy-7-[(4aS, 7aS)-octahydro-6H-pyrrolo [3,[4][5][6] pyridine-6-yl]-4-oxo-3-quinoline carboxylic acid, is a fluoroquinolone broad-spectrum antibiotic agent and used in conjunctivitis. A few analytical techniques have been constructed for quantification of several drugs based on literature survey such as UV Spectrophotometry [33][34][35][36] RP-HPLC [37][38][39][40] , HPLC [41][42] , HPLC-MS [43][44] , LC-MS 45 , LC 46 , chemiluminescence 47 , Tanden mass spectrometry 48 methods for determination of Moxifloxacin have been reported.…”
Section: Gemifloxacin Chemically Is [{Rs}7-[{4z}-3-{aminomethyl}-mentioning
confidence: 99%
“…It was found that the tailing effect is reduced and the elution time of SPAR was 10-fold lower in UPLC analysis. The number of theoretical plates was three times greater for UPLC than for HPLC The detection applied in chromatographic analysis were UV [ 17 , 53 , 54 ], diode array detector (DAD) [ 57 ], and MS [ 35 , 55 ]. The MRM employed in MS/MS analysis were: m / z 393.2 → 349.3 [ 35 ] and m / z 392.9 → 348.7 [ 55 ].…”
Section: Third Generation Fluoroquinolonesmentioning
confidence: 99%
“…The separation was performed on a C18 column. The analysed matrices via separation techniques were plasma, urine, serum, and tissues (muscle) [ 35 , 53 57 ]. The organic solvent applied in analysis was ACN [ 17 , 35 , 53 55 , 57 ].…”
Section: Third Generation Fluoroquinolonesmentioning
confidence: 99%
“…We hereby report the in vitro antimycobacterial activity of the previously reported N -substituted-glycinyl-1 H -1,2,3-triazolyl oxazolidinones and the development of a fast, reliable, and validated bio-analytical liquid chromatographic–mass spectrometric (LC-MS) method of analysis for estimating the plasma concentration of PH-189 in the presence of other biological constituents and to indicate any product(s) of instability. Literature survey showed that different instrumental methods have been reported for assessing analysis of structurally diverse oxazolidinone derivatives and their instability products in plasma [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%